Morphological variation of the female reproductive organs of the bat Artibeus lituratus during its different reproductive phases - Rodrigues, Alderrosy F.; Santiago, Cornélio S.; Morielle-Versute, Eliana [UNESP]; Taboga, Sebastião R. [UNESP]; Beguelini, Mateus R. (Wiley, 2019)
Artibeus lituratus is one of the most recognized bat species in the neotropics, probably due to its high abundance in urban areas. Despite its wide distribution, the morphology and physiology of its reproductive organs remain unclear. Thus, the aim of the present study was to describe the morphology and histology of the female reproductive organs of this species, and evaluate morphological variations during its different reproductive phases (nonreproductive, pregnant, lactating, etc.). Thirty adult females were collected, divided into six (6) sample groups, according to the reproductive status, and submitted to anatomical and histological analyses. We show that the ovaries of A. lituratus are polarized, present a low number of interstitial glands, have large and well-developed Graafian follicles and a persistent corpus luteum, and may present a functional everted corpus luteum. Ovulation is simple, unilateral and nonpreferential, possibly alternated in successive ovulations, and may be sequential, with the occurrence of postpartum estrus. The uterus is simplex, the implantation is fundic and interstitial and the placenta is chorioallantoic, discoidal, and hemochorial. The female reproductive organs of A. lituratus share similarities with the pattern observed in human, which indicates that A. lituratus may be an interesting animal model in reproductive studies.
Keywords: Chiroptera; ovary; reproduction; uterus